A review of the genus Aponema Jensen, 1978 (Nematoda: Microlaimidae) with description of three new species - Kovalyev, Shota V.; Miljutina, Maria A. (Zootaxa, 2009)
The taxonomy of the genus Aponema Jensen, 1978 is discussed. An emended diagnosis and identification keys at species level are provided. Two Aponema species – A. decramerae and A. mnazi are transferred from the genus Aponema to Microlaimus because of the presence of two testes. One known Microlaimus species, Microlaimus nanus Blome, 1982, is transferred from the genus Microlaimus to Aponema because of the presence of a single testis in males. Three new Aponema species are described. A. bathyalis sp. n. is characterized by a small body, smooth or slightly transversely striated cuticle, amphids with rod-like protruding corpus gelatum, almost round pharyngeal bulb and presence of three papilliform precloacal supplements in males. A. bathyalis is similar to A. nympha and A. nanum but differs from the former by the position of amphidial fovea (at about 1.5 head diameters from anterior end vs less than 0.7 head diameters from anterior in A. nympha) and from the latter by the presence of a gubernaculum, a protruding corpus gelatum from the amphidial fovea and by the shorter tail (c = 8.2–11.3 vs c = 5.8–7.8). A. minutissima sp. n. is characterized by a very small slender body, transversely striated cuticle, roundish amphidial fovea, spherical pharyngeal bulb, presence of short somatic setae, large spermatozoa, and a weakly developed copulatory apparatus without gubernaculum. It differs from the other Aponema species by the small body size (0.20–0.43 mm). It mostly resembles A. bathyalis sp. n. but differs by smaller size, slightly striated cuticle and absence of a gubernaculum. A. westindicum sp. n. is characterized by a larger body, annulated cuticle, discernible dorsal tooth, pyriform pharyngeal bulb and conical tail. It differs from A. nanum (Blome, 1982) by longer body size and structure of buccal cavity. All Aponema species described in this paper are characterized by monorchic males without gubernacular apophyses, females with two outstretched ovaries and a conical tail.